Determinants of Audit Quality: The Role of Auditor Independence, Competence, and Professional Ethics in Public Accounting Firms in Indonesia - Tommy Kuncara; Poso Nugroho; Fera Riske Anggita (International Journal Multidisciplinary Science, 2026)
Audit quality has become an increasingly critical issue in maintaining public trust in financial reporting, especially in Public Accounting Firms in Indonesia. Several audit failure cases in corporate financial statements indicate that auditors do not always succeed in detecting material misstatements effectively. This condition raises concerns regarding the role of auditor independence, competence, and professional ethics in ensuring reliable audit outcomes. Therefore, this study aims to analyze the effect of auditor independence, competence, and professional ethics on audit quality in Public Accounting Firms in Indonesia. This study employs a quantitative research approach using a survey method. Primary data were collected through questionnaires distributed to auditors working in Public Accounting Firms. The data were analyzed using multiple linear regression analysis to examine the relationship between independent variables and audit quality. The results show that auditor independence, competence, and professional ethics have a positive and significant effect on audit quality. Among these variables, professional ethics is found to be the most dominant factor influencing audit quality. This indicates that ethical behavior plays a crucial role in ensuring audit integrity and reliability, beyond technical competence and independence. The implications of this study suggest that Public Accounting Firms should strengthen ethical standards, improve auditor competence through continuous professional training, and maintain auditor independence to enhance audit quality. These efforts are essential to improve public trust in audited financial statements and strengthen the credibility of the auditing profession. The originality of this study lies in the integrated analysis of auditor independence, competence, and professional ethics within a single empirical model in the context of Public Accounting Firms in Indonesia. This study contributes to auditing literature by providing comprehensive evidence that audit quality is shaped not only by technical factors but also by ethical and behavioral dimensions of auditors.